2019
DOI: 10.1080/19427867.2019.1662561
|View full text |Cite
|
Sign up to set email alerts
|

The impact of autonomous vehicles on urban traffic network capacity: an experimental analysis by microscopic traffic simulation

Abstract: Urban commuters have been suffering from traffic congestion for a long time. In order to avoid or mitigate the congestion effect, it is significant to know how the introduction of autonomous vehicles (AVs) influence the road capacity. The effects that AVs bring to the macroscopic fundamental diagram (MFD) were investigated through microscopic traffic simulations. This is a key issue as the MFD is a basic model to describe road capacity in practical traffic engineering. Accordingly, the paper investigates how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(105 citation statements)
references
References 24 publications
2
101
0
2
Order By: Relevance
“…Macro traffic models have been used to show that traffic capacity would be increased up to 36% if all vehicles were automated. A different study from Lu et al (2019) has found similar figures (23% increase of capacity) but using traffic micro simulation.…”
Section: And What's About the Impact Of Cavs On Traffic?mentioning
confidence: 62%
“…Macro traffic models have been used to show that traffic capacity would be increased up to 36% if all vehicles were automated. A different study from Lu et al (2019) has found similar figures (23% increase of capacity) but using traffic micro simulation.…”
Section: And What's About the Impact Of Cavs On Traffic?mentioning
confidence: 62%
“…The challenges of urbanisation, if unmet urgently, would entail grave economic and environmental impacts [43]. FAGVs are expected to improve mobility and traffic conditions in cities [94]. Therefore, it is urgent to develop FAGVs integrated with SC to address those challenges and improve our daily commute.…”
Section: Resultsmentioning
confidence: 99%
“…This equation is only valid for freeways, whereas equations for multi-lane highways, signalized highways and other road types can be found in HCM2016 [43]. It is worth mentioning that the spread of autonomous vehicle will change the capacity formula in the future because the throughput of road segments will be increased due to better resource utilization [44], [45], [46].…”
Section: Flow-speed Ratio-based Congestion Definitionmentioning
confidence: 99%